2001
DOI: 10.1038/sj.cgt.7700368
|View full text |Cite
|
Sign up to set email alerts
|

Efficient and cancer-selective gene transfer to hepatocellular carcinoma in a rat using adenovirus vector with iodized oil esters

Abstract: Gene therapy for cancer requires efficient, selective gene transfer to cancer cells. In gene therapy for hepatocellular carcinoma ( HCC ) , gene transfer is efficient for small tumors, but not for large tumors. The delivery of anticancer agents and of iodized oil esters as embolic agents through tumor -feeding arteries is known as transarterial embolization. We speculate that genes may be efficiently and selectively transferred for HCC using iodized oil esters because these esters may remain together with a ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…Similar results were observed in phase I/II clinical studies of NSCLC or advanced breast cancer patients receiving intratumoral Ad-p53 injections combined with chemotherapy (Roth, 2006). The hepatic arterial infusion of an emulsion of iodized oil and Ad-p53 causes exogenous wt-p53 expression (Shiba et al, 2001). An in vitro study indicated that adenovirus-mediated p53 gene transfer promotes G 1 -phase arrest and cell apoptosis, thereby sensitizing hepatocellular carcinoma cells to heavy-ion irradiation (Liu et al, 2007) or CaSki human cervical cancer cells to photodynamic therapy (Lim et al, 2006).…”
Section: Tablesupporting
confidence: 69%
“…Similar results were observed in phase I/II clinical studies of NSCLC or advanced breast cancer patients receiving intratumoral Ad-p53 injections combined with chemotherapy (Roth, 2006). The hepatic arterial infusion of an emulsion of iodized oil and Ad-p53 causes exogenous wt-p53 expression (Shiba et al, 2001). An in vitro study indicated that adenovirus-mediated p53 gene transfer promotes G 1 -phase arrest and cell apoptosis, thereby sensitizing hepatocellular carcinoma cells to heavy-ion irradiation (Liu et al, 2007) or CaSki human cervical cancer cells to photodynamic therapy (Lim et al, 2006).…”
Section: Tablesupporting
confidence: 69%
“…15,40 Likewise, some attempts to apply chemotherapy or embolotherapy via tumor artery infusion have been made to obtain optimal effectiveness of antitumor therapy. [40][41][42][43] In summary, a combined approach of the Tf-TfR system with interventional catheter techniques enhanced the efficiency of p53 gene transfer to hepatic tumor in rabbit VX2 tumor models. The dual-target-oriented gene delivery may be an effective means for therapeutic gene therapy for human hepatocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, our contrast medi- um is quite different from other iron nanoparticles that accumulate at the lesion by phagocytosis 14) because a large amount of other iron nanoparticles are required to detect vascular lesions. Finally, this drug delivery system theoretically accommodates both contrast medium and agent for treatment, therefore enabling us to simultaneously detect and treat vascular lesions 25,26) . Furthermore, this particle can be modified to deliver agents to the target tissue more precisely 27) .…”
Section: Discussionmentioning
confidence: 99%